2019
DOI: 10.3389/fimmu.2019.00448
|View full text |Cite
|
Sign up to set email alerts
|

Bystander T-Cells Support Clonal T-Cell Activation by Controlling the Release of Dendritic Cell-Derived Immune-Stimulatory Extracellular Vesicles

Abstract: Extracellular vesicles (EV) that are released by immune cells are studied intensively for their functions in immune regulation and are scrutinized for their potential in human immunotherapy, for example against cancer. In our search for signals that stimulate the release of functional EV by dendritic cells we observed that LPS-activated human monocyte-derived dendritic cells (moDC) changed their morphological characteristics upon contact with non-cognate activated bystander T-cells, while non-activated bystand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…Similar to T cells and B cells, natural killer (NK) cells can rapidly respond to hantavirus infection beyond the level that is normally observed with other virus infections [20,71]. In turn, these bystander-activated immune cells may license uninfected DCs cross-presenting hantaviral antigen to initiate hantavirus-specific (TCR-dependent) T-cell activation and expansion [72,73].…”
Section: Immunological Consequences Of Hantavirus Infection Of Dcsmentioning
confidence: 99%
“…Similar to T cells and B cells, natural killer (NK) cells can rapidly respond to hantavirus infection beyond the level that is normally observed with other virus infections [20,71]. In turn, these bystander-activated immune cells may license uninfected DCs cross-presenting hantaviral antigen to initiate hantavirus-specific (TCR-dependent) T-cell activation and expansion [72,73].…”
Section: Immunological Consequences Of Hantavirus Infection Of Dcsmentioning
confidence: 99%
“…DC-derived EV are capable of inducing T-cell responses, through presentation of antigenic peptides on MHC molecules [ 2 , 4 , 5 , 10 , 11 , 17 , 37 , 38 ]. We recently demonstrated that non-cognate interactions between DC and bystander T-cells modulates third party antigen-specific T-cell responses via EV, possibly also involving EV mediated transfer of miR-155 [ 17 ]. The microRNA miR-155 is a critical regulator of adaptive immune responses [ 39 ], exemplifying a mechanism of how antigen presentation via intercellular transfer of EV may promote adaptive immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the precise role that DC-derived EV play in vivo remains unclear. Previously, we reported that interactions of DC with activated T-cells stimulated the release of antigen presenting EV, suggesting a role EV in dissemination and reinforcement of antigen presenting potential within lymphoid tissues [16,17]. Another hint for antigen presenting functions of EV came from observations that both macrophages and epithelial cells can release phagocytosed pathogens through non-lytic expulsion, involving direct fusion of the phagosome with the plasma membrane [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…A study showed that exosomes from LPS-treated dendritic cells endowed B cells with the ability to activate naive T cells in vitro and primed naive T cells via MHC class II and ICAM-1 in vivo ( 56 ). Another study showed that exosomes from LPS-challenged dendritic cells encountered with activated T cells were enriched in miR-155, HLA-I and ICAM-1, and were able to activate peptide-specific CD8 + T-cells ( 57 ).…”
Section: Impact Of Exosomes On Immune Cellsmentioning
confidence: 99%